Uso y percepción de comunidades campesinas sobre mamíferos Silvestres en ecosistemas de alta montaña, Génova, Quindío (2012)
Traditional knowledge reflects on how human communit ies relate to the environment, this knowledge is represents for perception, attitude and usage. Our study aims to determine and compare the perception, attitude and use of wild mammals from peasant inhabitants of the villages of Rio Rojo, San Juan, Rio Gris and Pedregales of Genova municipality, department of Quindío. Between May and August 2011, we visited 18 farms in four villages where semiestructured interview were realized. We determined species recognition, patterns of perception, attitude, use and importance level from children and farmers. First we calculated the importance in use based on the Rate of Cultural Significance in each village and then on th e total global sampling area (RCS-RCST). The farmers identified 27 species of mammals where twelve have use as food, medicine, ornament or pets. Hunting is semi-subsistence and highest RCST species were: Nasua nasua (RCST 0.26), Nasuela olivacea (RCST 0.26), Cuniculus taczanwoski (RCST 0.21), Dasypus novemcinctus (RCST 0.16) and Mazama rufina (RCST 0.11). Eight species are known to cause conflicts: Puma concolor, Nasua nasua, Nasuela olivacea, Cerdocyon thous, Tremarctos ornatus, Mustela frenata, Sciurus granatensis and Didelphis pernigra. P. concolor represents the highest hunting pressure and negative perception from inhabitats. The hunting pressure on wild mammals has declined in recent years, even though there are still people who are hunting. The positive p erception about the wild mammals is predominant from inhabitants in the area. This may be an opportunity to advance focusing on conservation efforts with the participation of the community. These actions may be aimed toward implementing strategies to red uce conflict human-animal, lower hunting and strengthen programs for the protection of habitats.